Sistem Informasi Pengaduan Masyarakat Berbasis Web Pada Kantor Desa Ladang Peris Kecamatan Bajubang - Kurniasih, Kurniasih; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2022)
The Ladang Peris Village Office, Bajubang District, has not used the computerized system and complaint process used by the village office by taking notes. In delivering information to the community, the Ladang Peris Village Office, Bajubang District, still uses the information board placed in the village office. In addition, to serve public complaints, the Ladang Peris Village office uses the complaint counter to be submitted directly to village officials regarding the village agenda, rural development plans, information on damaged roads, disaster-prone locations. In addition, there is no media to introduce rural tourism to outsiders, and there is no media information regarding fundraising from donors. The existing constraints cause the performance of village officials at the Ladang Peris Village Office to be relatively long, the information that should be conveyed to the community is not channeled properly and makes it difficult for the community to make complaints, it is necessary to use website technology to support the reporting process that can be used by village officials and the community in Peris Farm Village, Bajubang District. The application of technology, especially the public complaint information system, will facilitate the device by reducing limitations in providing services to the community